2005
DOI: 10.1007/s10447-005-2252-0
|View full text |Cite
|
Sign up to set email alerts
|

Role Behavior Profiles of Israeli School Counselors

Abstract: This study of 681 school counselors in Israel examines how counselors allocate their time between counseling tasks and whether their role behavior can be characterized according to distinctive profiles. Three distinctive profiles of role behavior were identified: The traditional profile (40% of the sample), in which individual counseling to students was prominent; the prevention profile (20% of the sample), in which a guidance curriculum with an emphasis on prevention programs was preva1ent; and the balanced p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…This may have been particularly salient for participants because of struggles within their roles as counselors, a theme that seemed to stand out in the results. For instance, if as the literature (Rifenbary 1997) states, counselors are required to allocate more time on college preparation or other academic and scheduling related issues, the limited designated time in addressing personal counseling needs may have intensified the saliency of these issues for the counselors (Erhard and Harel 2005). Limited understanding of the personal counseling role may have also heightened the counselors' concerns with regards to their counseling competency and professional development (Rifenbary 1997).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This may have been particularly salient for participants because of struggles within their roles as counselors, a theme that seemed to stand out in the results. For instance, if as the literature (Rifenbary 1997) states, counselors are required to allocate more time on college preparation or other academic and scheduling related issues, the limited designated time in addressing personal counseling needs may have intensified the saliency of these issues for the counselors (Erhard and Harel 2005). Limited understanding of the personal counseling role may have also heightened the counselors' concerns with regards to their counseling competency and professional development (Rifenbary 1997).…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, various authors have noted several challenges related to counselor professional development in countries outside the USA. For instance, in reflecting on the state of counseling in settings such as Israel (Erhard and Harel 2005;Lazovsky and Shimoni 2007;Mar'l 1988), India (Natrajan and Thomas 2002;Chaudhary and Bansal 2000;Unnithan 1986), Hong Kong (Hue 2007;Leung et al 2007;Hui 2000), Kuwait (Abal and Hornby 1995;Al-Sarraf 1993;Abu-Eita and Sherif 1990), Australia (Humes 1991;McMahon and Patton 2001), Greece (Dimakos 2006;Giordano 1997), Pakistan (Choudhry et al 2008;Jimerson et al 2007;Almas and Ibrahim 1985), authors highlight the limited role that school counselors play in addressing students' mental health needs. Some authors speak to limited counselor training and a lack of clarity in school counselor roles, whereas others highlight the notion that mental health issues are seen as inconsequential alongside higher educational expectations.…”
Section: Professional Needs Of International School Counselorsmentioning
confidence: 96%
“…The findings are not consistent: whilst research has shown a relationship between these variables (cf., Eyal 1976;Weizner 1983), more recent studies have not shown such a relationship (cf., Erhard and Harel 2005;Shemer-Elkayam and Erhard 2004). Counselors' training, as the major form of professional socialization, has been found to impact their general role perception (ShemerElkayam and Erhard 2004) and perception of being social activists in particular (cf., Bemak and Chung 2005;Chung and Bemak 2012;Corey 2010;Dixon et al 2010).…”
Section: Personal Characteristics Of Counselorsmentioning
confidence: 96%
“…For example, counselors in schools with a high proportion of immigrants devote more time to multicultural counseling (Baron 1999;Erhard and Harel 2005).…”
Section: Organizational Characteristics Of Schoolsmentioning
confidence: 99%
“…A proper balance between needs and preferences on the one hand, and the commitment to effective preparation of future counselors on the other, should be kept in mind. This is especially important in light of the transformations the school counseling profession is undergoing in Israel (Erhard & Harel, 2005) and in other countries such as the USA (American School Counselor Association, 2003;Erford, 2003), Scotland (Howieson & Sempel, 2000), and the UK (Bor, EbnerLandy, Gill, & Brace, 2000), highlighting the need to be informed about the preferred and necessary ways of performing the counselor role.…”
Section: Discussionmentioning
confidence: 97%